Successions to the Estates of Deceased Individuals in the Chilean Private International Law System - Picand Albónico, Eduardo (Revista Tribuna Internacional, 2020)
Successions to the estates of deceased individuals governed by more than one legal system – i.e., international successions - have increased significantly in recent years as a result of the free flow of people, assets and capital. Immigration in Chile has played a key role in increasing international private relations. In fact, our country has become in recent years a host country to many foreigners from different countries around the world, which has changed Chile by turning it into a multicultural society. At the same time, many Chileans have moved to foreign countries where they have started new families, with their assets usually being scattered among different countries. As a result of immigration, international successions have increased their complexity, rendering it essential for legal practitioners to identify the relevant court and applicable laws. The Chilean legislator (Chilean Civil Code of 1855) abides in this matter by the principle of unity and universality of successions to the estates of deceased individuals, whereby the heirs are successors of the deceased and there should therefore be one succession only, regardless of where the assets are located. The main standard is Article 955 of the Chilean Civil Code, which article sets forth that the succession is governed by the laws of the last place where the testator was domiciled. This same standard applies to the international jurisdiction.